Mass Production of LiFePO4/C Powders by Large Type Spray Pyrolysis Apparatus and Its Application to Cathode for Lithium Ion Battery - Shinsuke Akao; Motofumi Yamada; Takayuki Kodera; Takashi Ogihara (International Journal of Chemical Engineering)
Spherical LiFePO4/C powders were successfully produced at a rate of 100 g/h using a large type spray pyrolysis apparatus. Organic compounds such as citric acid and sucrose were used as carbon sources. Scanning electron microscopy observation showed that they had a spherical morphology with nonaggregation. X-ray diffraction analysis revealed that the olivine phase was obtained by heating at 600∘C under argon (95%)/hydrogen (5%) atmosphere. The chemical composition of LiFePO4/C powders was in good agreement with that of the starting solution. Electrochemical measurement revealed that the use of citric acid was most effective in ensuring a high rechargeable capacity and cycle stability. The rechargeable capacity of the LiFePO4/C cathode obtained using citric acid was 155 mAh/g at a discharge rate of 1 C. Because of the good discharge capacity of the LiFePO4/C cathode, it exhibited excellent cycle stability after 100 cycles at each discharge rate. Moreover, this high cycle stability of the LiFePO4/C cathode was maintained even at 50∘C.